2013
DOI: 10.1007/s12020-013-0127-4
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of hypopituitarism in tertiary care institutions in Turkish population: analysis of 773 patients from pituitary study group database

Abstract: Hypopituitarism in adult life is commonly acquired and the main causes are known as pituitary tumors and/or their treatments. Since there are new insights into the etiology of hypopituitarism and presence of differences in various populations, more studies regarding causes of hypopituitarism are needed to be done in different ethnic groups with sufficient number of patients. Therefore, we performed a multi-center database study in Turkish population investigating the etiology of hypopituitarism in 773 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 30 publications
5
32
0
2
Order By: Relevance
“…Tanriverdi et al presented a study related to the etiology of hypopituitarism in the Turkish population, by analyzing 773 hypopituitary adult patients [31]. That study has shown that nontumoral disorders were the most common causes of pituitary dysfunction among all the patients (43%).…”
Section: Discussionmentioning
confidence: 99%
“…Tanriverdi et al presented a study related to the etiology of hypopituitarism in the Turkish population, by analyzing 773 hypopituitary adult patients [31]. That study has shown that nontumoral disorders were the most common causes of pituitary dysfunction among all the patients (43%).…”
Section: Discussionmentioning
confidence: 99%
“…SS remains a frequent and probable cause of hypopituitarism in undeveloped and developing countries, but due to improvements in obstetric care, it is rare in developed countries. A recent study performed in Turkey showed that the frequency of SS was 13.8% among 773 patients with hypopituitarism [2], whereas a retrospective nationwide investigation in Iceland reported SS in only 5.1 of 100 000 women [3].…”
Section: Introductionmentioning
confidence: 96%
“…Predisposing factors for postpartum pituitary necrosis or Sheehan's syndrome are for women who delivered at home, women with severe postpartum hemorrhage who are given a blood transfusion, women with higher number of pregnancies and deliveries, those with genetic factors involved in the coagulation cascade and those with small sella size (35,36). Recent Turkish study showed that Sheehan's syndrome was present in 13.8% of patients with hypopituitarism, compared with 3.1% in developed countries (37,38). The onset of hypopituitarism is usually insidious, and there is often a delay in diagnosis of several decades (a median delay is 10 years).…”
Section: Sheehan's Syndrome -The Postpartum Pituitary Necrosismentioning
confidence: 99%